No Early Effect of Intrathecal Rituximab in Progressive Multiple Sclerosis (EFFRITE Clinical Trial) - Bonnan, Mickael; Ferrari, Sylvie; Courtade, Henri; Money, Paul; Desblache, Pauline; Barroso, Bruno; Debeugny, Stéphane (Multiple sclerosis international, 2021)
Background. The progressive phase of multiple sclerosis (MS) is characterized by an intrathecal (IT) compartmentalization of inflammation, involving B-cells within meningeal follicles, and resisting all the available immunosuppressive treatments. A new therapeutic paradigm may be to target this inflammation by injecting immunosuppressive drugs inside the central nervous system compartment. Methods. We designed a single-center, open-label, randomized, controlled, phase II study designed to evaluate the safety and efficacy of IT rituximab in progressive MS (EFFRITE trial; ClinicalTrial Registration NCT02545959). Patients were randomized into three arms (1 : 1 : 1): control group, IT rituximab (20 mg, IT) group, and intravenous+IT (IV+IT) group. The main outcome was a change in levels of CSF biomarkers of inflammation (osteopontin). Secondary outcomes were changes in levels of CSF biomarkers of axonal loss (neurofilament light chain) and clinical and MRI changes. Results. Ten patients were included (2 : 4 : 4). No adverse event occurred. OPN level remained stable in CSF at each time point, whereas NFL had slightly decreased (-8.7%) at day 21 (p=0.02). Clinical parameters remained stable and leptomeningeal enhancements remained unchanged. Conclusion. Clinical outcome and biomarkers of inflammation were not dramatically modified after IT injection of rituximab, probably due to its limited efficiency in CSF. Drug issues for future studies are discussed.